Management of Sars-Cov-2 Medical Waste Against a Covid19 Pandemic in Indonesia: A Literature Review - Moch. Irfan Hadi; Mirna Widiyanti; Mei Lina Fitri Kumalasari; Muhammad Yusuf Alamudi; Dedy Suprayogi (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: SARS-CoV-2 RNA transmission in wastewater has a risk of fecal transmission of SARS-CoV-2 to humans and the environment. Despite the increasing number of cases in almost all areas in Indonesia, the study to review and evaluate waste management resulted from medical facilities is still limited and less explored. This literature review aims to analyze the applicability of WHO guidelines on wastewater management to be implemented in Indonesia. Scientific papers were collected from several electronic databases such as PubMed, PLoS, Researchgate, WHO, Elsevier, Science, SARS-CoV-2, Covid19, and wastewater. The articles were selected based on the inclusion criteria that use SARS-CoV-2, Covid19, and wastewater as the main variables observed. The articles published before 2013 were excluded from this review. Discussion: Wastewater monitoring of SARS-CoV-2 within medical and health facilities is implemented to identify the virus's presence as the causative agent of Covid19 disease, which contaminated the environment and society. The results of the analysis in wastewater can be used to determine the infection control in health facilities while also beneficial in formulating the monitoring of environmental impacts caused by the waste. These efforts would support policies or interventions based on public health by applying social distances, locking, quarantine areas that aim to break the Covid19transmission. Conclusion: Briefly, by considering the urgency of Covid19 pandemic containment and control measures of transmission in health facilities, population and environment. It is a waste management guideline that is highly required to be implemented based on public health aspects.